The use and misuse of income data and extreme poverty in the United States - Bruce D. Meyer; Derek Wu; Victoria R. Mooers; Carla Medalia (American Enterprise Institute (AEI), 2019)
More than half of all misclassified households have incomes from the administrative data above the poverty line, and several of the largest misclassified groups appear to be at least middle class based on measures of material well-being. In contrast, the households kept from extreme poverty by in-kind transfers appear to be among the most materially deprived Americans.
Keywords: A; 330; Poverty; household income